PERANCANGAN PROTOTIPE SIMULATOR LANDING GEAR SYSTEM PESAWAT TERBANG AIRBUS A320 BERBASIS MIKROKONTROLER - BAMBANG SETIAWAN; MUNNIK HARYANT; AGUS SUGIHARTO (JURNAL TEKNIK INDUSTRI, 2021)
This research is intended to make a prototype simulator or props from one of the systems contained in an aircraft so that students can clearly understand the system that has been delivered. And making this tool can be a reference that the micro controller system can be used to realize the sophisticated systems contained in aircraft so that in the future it can be improved or applied in the aircraft industry.Keywords: landing gear system, micro controller atmega 8535, simulator, hydraulic